2002
DOI: 10.1016/s0022-2836(02)00172-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Membrane Targeting of the Flagellar Export ATPase FliI: Interaction with Acidic Phospholipids and FliH

Abstract: The specialised ATPase FliI is central to export of flagellar axial protein subunits during flagellum assembly. We establish the normal cellular location of FliI and its regulatory accessory protein FliH in motile Salmonella typhimurium, and ascertain the regions involved in FliH(2)/FliI heterotrimerisation. Both FliI and FliH localised to the cytoplasmic membrane in the presence and in the absence of proteins making up the flagellar export machinery and basal body. Membrane association was tight, and FliI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
87
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 32 publications
(49 reference statements)
7
87
0
3
Order By: Relevance
“…2B). Coomassie blue staining confirmed that outer membrane proteins located toward the bottom of the gradient, and immunoblotting revealed both the N⌬120-140 and N⌬130-140 in the inner-membrane fractions colocalizing with the NADH oxidase and flagellar C-ring component FliM (27,28).…”
Section: Dominant-negative Export-defective Chaperone Variants Localimentioning
confidence: 82%
See 3 more Smart Citations
“…2B). Coomassie blue staining confirmed that outer membrane proteins located toward the bottom of the gradient, and immunoblotting revealed both the N⌬120-140 and N⌬130-140 in the inner-membrane fractions colocalizing with the NADH oxidase and flagellar C-ring component FliM (27,28).…”
Section: Dominant-negative Export-defective Chaperone Variants Localimentioning
confidence: 82%
“…E. coli total phospholipids (Avanti Polar Lipids) were prepared by sonication (27). Purified proteins (1-2 g) were mixed with 40 l of 10 mg⅐ml Ϫ1 lipid in Tris-buffered saline (20 mM Tris, pH 7.4͞150 mM NaCl͞TBS) (27) and incubated at room temperature for 15 min.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…FliI shows extensive similarity to the a/b subunits of proton-driven F 0 F 1 -ATPase for its entire molecular structure 6 , although sequence similarity is limited to their respective ATPase domains 7,8 . Unlike F 1 -ATPase, however, which forms the a 3 b 3 hexameric ring, FliI self-assembles into a homohexamer 9,10 . When FliI oligomerization is suppressed by a small deletion in its amino-terminal region, flagellar protein export does not occur efficiently, suggesting that FliI hexamerizes on docking to the export gate made of the six integral membrane components, for which the cytoplasmic domains of FlhA and FlhB are thought to form the docking platform 11 .…”
mentioning
confidence: 99%